Emerging trends in pectin functional processing and its fortification for synbiotics: A review. (April 2023) - Sun, Rui; Niu, Yefan; Li, Menghui; Liu, Yuanye; Wang, Kai; Gao, Zhenpeng; Wang, Zhouli; Yue, Tianli; Yuan, Yahong
Abstract: Background: Pectin is a natural prebiotic with great potential for encapsulating probiotics to prepare synbiotics. Despite that the variety of raw materials and the output of agricultural by-products facilitating the acquisition of pectin with desirable physicochemical properties are increasing, low coverage processing technologies and the lack of accurate mechanistic guidance lead to many resources not being underutilized. Furthermore, the structural basis of pectin in the prepared microsystems and its effects on the viability of probiotics under gastrointestinal digestive conditions and storage stability have not been systematically elucidated. Scope and approach: This review discusses the rationalization of steps and sequences of pectin processing, the suitability of emerging technological applications, and the relationship between structure and intended function, involving three stages: pretreatment, extraction, and post-processing, aiming to improve the access of pectin and developing new bioavailability opportunities. Subsequently, multiple possibilities for pectin-based synbiotics are enumerated. The preparation methods, structural characteristics, and protective capacity against probiotics of pectin microsystems are analyzed, focusing on the role of pectin as a cell wall material. Key findings and conclusion: Collating, comparing, and inferring the similarities and differences of various factors in pectin extraction and processing improves resource utilization. Natural deep eutectic pretreatment is beneficial for subsequent water extraction, which can improve the extraction efficiency of ohmic heating. The right treatment sequence for emerging technologies enables pectin with unique rheological properties and prebiotic activity. Probiotic entrapment by pectin-coated metal nanoparticles significantly reduces the pore size of the microcapsules. Therefore, developing pectin-based synbiotics is important for protection of probiotic viability and promotion of human health. Graphical abstract: Image 1 Highlights: Precise application of emerging technologies improves pectin access and bioavailability. Advanced synbiotic systems were constructed based on prebiotic activity and structural strength of pectin. Introduction of pectin synbiotics into intestine contributes to regulate gut microbiota produce health-beneficial metabolites. Protective effect of pectin as wall material on probiotic during gastrointestinal digestion and storage were explored. Future development strategies and possibilities of pectin-based synbiotics were highlighted.